7-(2,4-Dichlorophenyl)-2-methylsulfanylpyrazolo[1,5-a]pyrimidine-3-carbonitrile - Li-rong Wen; Shu-wen Wang; Huai-yuan Xie (Acta Crystallographica Section E, 2009)
In the molecule of the title compound, C14H8Cl2N4S, all the ring atoms in the pyrazolopyrimidine system are almost coplanar, the largest deviation from the mean plane being 0.027 (2) Å for a C atom. The conformation of the methylsulfanyl group is antiperiplanar, with a torsion angle of −176.7 (2)°. A weak intermolecular C—H...N hydrogen bond and a Cl...N halogen bond [Cl...N = 3.196 (5) Å] with a nearly linear N...Cl—C angle [174.2 (1)°] link the molecules into a two-dimensional assembly. Face-to-face π–π stacking, with a centroid–centroid separation of 3.557 (2) Å and an angle of 7.1 (1)° between the two planes, completes the intermolecular interactions in the solid state.